Analisis Dampak Ekologis Proyek ODA Jepang di Indonesia dalam Mendukung Pembangunan Dunia Berkelanjutan (2012-2018) - Ni Made Citra Kusuma Dewi (Universitas Airlangga, 2020)
Japan is the biggest donor for Indonesia. Under bilateral cooperation, Japan has actively sent foreign aids to Indonesia within the framework of Official Development Assistance (ODA) since 1960s. By receiving assistance worth 45% of the total foreign aid received by Indonesia, Japan is also considered important in various Indonesian national development programs. Along with the commitment to support Sustainable Development Goals, Japan also contributes in funding various projects which aim to increase the environmental quality and sustainability of Indonesia. Although not all Japanese assistance to Indonesia is specifically aimed at addressing environmental issues, it cannot be denied that every Japanese ODA project has its own ecological impact on Indonesia.Departing from the case, the author will analyze the extent to which Japanese foreign aid to Indonesia has an impact on environmental conditions in Indonesia. The author groups Japanese ODA projects in five categories, namely: (1) environmental strictly defined (ESD); (2) environmental broadly defined (ESD); (3) neutral (N); (4) dirty broadly defined (DBD); and (5) dirty strictly defined (DSD). Based on the data collected, the authors found that the Japanese ODA project had varied ecological impacts for Indonesia. Therefore, the authors argue that Japanese ODA projects in Indonesia not only have positive implications, but also negative implications for the environment.